Acceptance Test of Jokowi's Herbal Beverage with Antioxidant Properties in Isotonic Beverage Formulation - Yoewono, Jessica Renata; Krisbianto, Oki; Sugiharto, Yurika; Ridfan, Lorent Permata (Jurnal Ilmu Pangan dan Hasil Pertanian, 2023)
A herbal beverage mixture based on extracts of turmeric (Curcuma longa), Javanese turmeric (Curcuma xanthorrhiza), and red ginger (Zingiber officinale) with a ratio of 8:6:3 was developed as an isotonic beverage after describing its sensory characteristics and antioxidant properties. Three different dilutions (1:10, 1:15, and 1:20) were used for sensory acceptance testing by consumers. Antioxidant activity tests using DPPH followed by HPLC were conducted on each extract as well as the most concentrated dilution and the best treatment. The sensory testing results indicated that the 1:20 dilution treatment was the most acceptable. The DPPH results showed that the 1:10 and 1:20 dilutions had inhibition activities of 52.34% and 37.94% respectively, which correlated with the quantification of curcumin using HPLC, namely 167.47 Âµg/g and 125.06 Âµg/g. The higher the curcumin content, the higher the DPPH inhibition activity. Atomic absorption spectroscopy (AAS) analysis revealed that the Na and K content in the 1:20 diluted herbal beverage were 11.66 mg/kg and 13.85 mg/kg respectively, which were still lower than the standard SNI-01-4452-1998. Therefore, the isotonic beverage was formulated by adding low-sodium salt and sodium citrate as sources of sodium, potassium, and citrate.